The Relationship Between Complementary Food Provision and Nutritional Status of Children (6-24 Months) in Sinunukan 1 Village, Sinunukan District, Mandailing Natal Regency in 2024 - Arniati123; Aswan, Yulinda; Yusro Pohan, Sakinah (Journal of Nutrition and Public Health, 2026)
Background: Undernutrition is a nutritional problem caused by an imbalance between food intake and energy and nutrient needs, particularly protein. Globally, 148.1 million children under 5 years of age suffer from malnutrition, with 45.6 million of them experiencing wasting. In Indonesia, children's health is a primary concern because their health status reflects the future of the nation's development. One of the determinants of optimal nutritional status in children aged 6-24 months is the appropriate provision of complementary foods (MPASI). Aims: This study aims to determine the relationship between the provision of complementary foods with breast milk and the nutritional status of children aged 6-24 months in Sinunukan 1 Village, Sinunukan District, Mandailing Natal Regency in 2024. Methods:This research is quantitative with an observational analytical design using a cross-sectional approach. The population and sample size included 40 mothers with children aged 6-24 months in Sinunukan 1 Village, selected using a total sampling technique. The instruments used included questionnaires and anthropometric measurements. Data analysis was performed using the chi-square statistical test. Result: The results showed that the majority of respondents (62.5%) provided appropriate complementary foods, with 47.5% of them having children with normal nutritional status. Conversely, in the inappropriate complementary food category (37.5%), 27.5% of children had abnormal nutritional status. The chi-square test obtained a p-value of 0.002 (p < 0.05). Conclusion: There is a significant relationship between the provision of complementary foods with the nutritional status of children aged 6-24 months in Sinunukan 1 Village, Sinunukan District, Mandailing Natal Regency in 2024. Mothers are expected to pay more attention to the appropriateness of providing complementary foods so that children avoid problems with abnormal nutritional status.